Argumentative and aggressive communication : theory, research, and application - Rancer, Andrew S. (Sage Publications, 2006)
This book is devoted to the theory-building research and application issues on aggressive communication. In addition to fully describing the two predispositions and their measurement, it synthesizes the large corpus of research in several communication contexts, including family, organizational, intercultural, instructional and mediated contexts.